THERMAL STRESSES AND MICROCRACKING IN CALCITE AND DOLOMITE MARBLES VIA FINITE ELEMENT MODELLING - Weiss T.; Siegesmund S.; Fuller E.R. (My University, 2002)
Microstructure-based finite element simulations were used to study the thermo-mechanical behaviour of calcite and dolomite marbles. For a given mineral microstructure, thermal stresses and elastic strain energy varied with the single-crystal elastic constants and coefficients of thermal expansion. Moreover, they were a strong function of crystallographic texture. Given the same morphological microstructure and crystallographic texture, calcite had larger thermal stresses and elastic strain energy than dolomite. Hence, calcite has an earlier onset of microcracking upon either heating or cooling, and has a greater extent of microcracking at a given temperature differential. However, the variation in thermal stresses and microcracking propensity for either mineral with different randomly assigned textures was greater than the variations between the two minerals. The measured bulk thermal expansion anisotropy suggested that the random representations had some degree of texture. Simulations using the actual texture of the real microstructure, as determined by electron-backscattered diffraction, showed the largest degree of bulk thermal expansion anisotropy, the smallest strain energy, and hence the smallest amount of thermal microcracking. Microstructure-based finite element simulations are considered an excellent tool for elucidating myriad influences of microstructure and physical properties on the thermal degradation of marbles and other rocks.